Evaluasi User Experience Pada Sistem Informasi Perpustakaan Menggunakan User Experience Questionnaire - Rondonuwu, Yeremia Victor; Kurniawan, David Thanlian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study evaluates the User Experience (UX) of the Library Information System at Pignatelli Triputra University using the User Experience Questionnaire (UEQ) to ensure that investment in the development of the library information system provides maximum benefits, minimizes user barriers, and enhances the effectiveness and efficiency of library operations. The study involved 30 students as respondents, measuring six components of user experience with average scores: attractiveness (1.61), clarity (1.84), accuracy (1.51), efficiency (1.88), stimulation (1.38), and novelty (0.88). The results indicate that clarity has the highest score, while novelty has the lowest, indicating the need for improvement in this area. The average scores for attractiveness, efficiency, and stimulation fall into the